A comprehensive review of binocular vision in myopia control - Srivastava, Namrata; Gupta, Deepak; Chandra, Mahesh (International Journal Of Community Medicine And Public Health, 2024)
Myopia is a growing problem worldwide and is particularly common among young people. Myopia is a disease that affects the retina responsible for detail in the middle eye and can lead to permanent vision loss. Myopia, a prevalent refractive error causing distant objects to appear blurred, is increasingly affecting global populations, particularly children. By 2050, it’s projected that half the world’s population will be myopic, largely due to genetic predispositions and environmental factors like excessive near work and limited outdoor activities. A promising approach to managing myopia is binocular vision training, which involves using both eyes to create a single, clear image, potentially slowing myopia progression. Understanding the benefits of this method is critical as we move forward, especially considering the surge in myopia cases during the COVID-19 pandemic due to increased digital device use. Research underscores the importance of addressing lifestyle and promoting outdoor activities and mitigating the impact of near work can help manage myopia progression and associated binocular vision disorders. Binocular vision training shows promise for myopia control by enhancing eye coordination, potentially slowing progression. Key factors include accommodation, AC/A ratios, and phoria, which are essential for effective diagnostics and therapy. Recent research emphasizes a holistic assessment of these elements for precise management of myopia and related binocular vision disorders in children. Understanding the mechanisms and innovative approaches of binocular vision in controlling myopia, highlighting the significance of continuous research and patient education in improving eye health.